2023
DOI: 10.1186/s13046-023-02644-x
|View full text |Cite
|
Sign up to set email alerts
|

CLDN6 inhibits breast cancer metastasis through WIP-dependent actin cytoskeleton-mediated autophagy

Abstract: Background As a breast cancer suppressor gene, CLDN6 overexpression was found to inhibit breast cancer metastasis in our previous studies, but the specific mechanism remains unclear. This study aimed to clarify the role and mechanism of CLDN6 in inhibiting breast cancer metastasis. Methods Western blot, immunofluorescence and transmission electron microscopy were performed to detect autophagy. Wound healing, transwell assays and lung metastasis mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…4 K) (Pearson correlation coefficient r = 0.795; Manders’ co-location coefficient M1 = 0.997 and M2 = 0.906). The colocalization criteria for two proteins were defined as follows: Pearson correlation coefficient r > 0.5 and Manders’ co-location coefficient M1 > 0.5, M2 > 0.5 [ 21 ]. Moreover, we validated the interactions between FAM171B and vimentin/HNRNPU in MB49 bladder cancer cells from mice.…”
Section: Resultsmentioning
confidence: 99%
“…4 K) (Pearson correlation coefficient r = 0.795; Manders’ co-location coefficient M1 = 0.997 and M2 = 0.906). The colocalization criteria for two proteins were defined as follows: Pearson correlation coefficient r > 0.5 and Manders’ co-location coefficient M1 > 0.5, M2 > 0.5 [ 21 ]. Moreover, we validated the interactions between FAM171B and vimentin/HNRNPU in MB49 bladder cancer cells from mice.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, CLDN6 was found to have an inhibitory function in breast cancer metastasis by upregulating WIP expression (WIP regulates the actin cytoskeleton autophagy pathways) during in vivo and vitro studies. This finding could explain why low levels of CLDN6 expression were found in metastatic breast cancer [101]. In colon cancer, CLDN6 activates the TYK2/STAT3 pathway, which might suppress the migration and invasion abilities of colon cancer cells [104].…”
Section: Role Of Claudins In Cancer Metastasismentioning
confidence: 95%
“…WIP colocalizes with LC3 and p-Arp3; breast cancer cells treated with CK666 exhibit reduced autophagic flux. Besides, WIP knockdown results in reduced LC3II expression and the number of autophagosomes, and makes the actin polymerizer Jaslakinolide lose its regulatory effect on autophagy, which indicates that actin cytoskeleton dependent on WIP to regulate autophagy [ 105 ]. WIP is not a member of NPFs in the traditional definition, but it affects actin assembly by regulating multiple NPFs (WASP, N-WASP, and cortactin) [ 104 ].…”
Section: Npfs and Autophagymentioning
confidence: 99%
“…However, Hasegawa et al confirmed that cortactin-mediated F-actin regulates autophagy without considering the influence of stimuli [ 101 ]. In our previous research, we found that WIP-mediated F-actin regulates autophagy without stimuli [ 105 ]. These studies indicated that NPFs can also regulate autophagy independently of stimuli.…”
Section: Npfs and Autophagymentioning
confidence: 99%